Cross-Country Empirical Studies of Systemic Bank Distress : A Survey - Demirguc-Kunt, Asli.; Detragiache, Enrica (Washington, D.C. : International Monetary Fund, 2005)
A rapidly growing empirical literature is studying the causes and consequences of bank fragility in present-day economies. The paper reviews the two basic methodologies adopted in cross-country empirical studies-the signals approach and the multivariate probability model-and their application to studying the determinants of banking crises. The use of these models to provide early warnings for crises is also reviewed, as are studies of the economic effects of banking crises and of the policies to forestall them. The paper concludes by identifying directions for future research.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet